2019
DOI: 10.7759/cureus.4048
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Dubin-Johnson Syndrome in Pregnancy

Abstract: Dubin-Johnson syndrome is an autosomal recessive condition characterized by recurrent episodes of jaundice and conjugated hyperbilirubinemia. It exacerbates during pregnancy and needs to be differentiated from other causes of jaundice. A 30-year-old patient presented to us with jaundice in her fourth pregnancy. She had intermittent episodes of jaundice earlier, with exacerbation in each pregnancy during the second trimester. The diagnosis of Dubin-Johnson syndrome was made on detailed evaluation along with his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Unlike other conditions that cause hyperbilirubinemia, such as liver disease, DJS does not typically cause pruritus, as serum total bile acid levels remain normal. In some cases, women with the condition may not exhibit any symptoms, but hyperbilirubinemia or obvious jaundice may develop when they start using oral contraceptives or become pregnant [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other conditions that cause hyperbilirubinemia, such as liver disease, DJS does not typically cause pruritus, as serum total bile acid levels remain normal. In some cases, women with the condition may not exhibit any symptoms, but hyperbilirubinemia or obvious jaundice may develop when they start using oral contraceptives or become pregnant [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the condition showed that the patient had been pregnant three times, and that yellow staining of the systemic skin, mucosa, and sclera was present during each pregnancy. The patient was diagnosed with acute cholecystitis, and the corresponding treatment was adopted, given the pregnancy factor[ 23 - 26 ]. The main pathological changes observed in the liver tissue were massive pigment particle deposition in hepatocytes and significant pigment granules in the central area of the lobules.…”
Section: Discussionmentioning
confidence: 99%
“…In women, the condition may be subclinical and only present with jaundice when contraceptives are used or when they are pregnant, with very few reports being the association between Dubin Johnson syndrome and pregnancy. [5][6][7][8][9][10] The clinical examination of patients is normal. Itching is not a symptom.…”
Section: Discussionmentioning
confidence: 99%
“…In the neonatal period the disease is rarely present and should only be suspected when there is unexplained hyperbilirubinemia of moderate to severe range and long evolution. 2,4,10…”
Section: Discussionmentioning
confidence: 99%